Analysis of physiological and kinematic demands of wheelchair basketball games - Seron, B. B.; Oliveira de Carvalho, E. M.; Greguol, M. (The Journal of Strength and Conditioning Research, 2019)
In wheelchair basketball (WB), knowledge of the specificities of the game is essential for efficient planning of training strategies for high performance. This study aimed to review the literature concerning studies that have investigated physiological and kinematic measures during WB games. The literature search took place in 4 electronic databases: Scopus, MEDLINE-PubMed, SPORTDiscus, and CINAHL. The inclusion criteria for this review were as follows: (a) articles that evaluated the behavior of physiological and kinematic variables during WB games; (b) athletes aged at least 18 years; and (c) participants with a minimum of 1 year in the modality practice. The selected studies (n = 16) were divided into 2 groups: physiological analysis (n = 11) and kinematic analysis (n = 5). In analyzing the studies, it was observed that the WB game is very demanding in relation to cardiovascular requirements (~65% of the time is spent in zones of high heart rate [HR] intensity and 70% of VO2peak). Edwards and Stagno methods seem to be adequate for the control of internal loads imposed on WB players, and moderate correlations were found between rating of perceived exertion measures and HR-based methods. Considering the methodological limitations, kinematic analysis in WB games is rather inconsistent (distance traveled between 2.6 and 5 km; average speed between 1.8 and 2.0 m/s; maximum speed = 4 m/s). Despite the gaps observed in this context, the execution of rotational movements seems to have great relevance for WB. We can conclude that different methods have been adequate for the internal load control in WB games. However, the results of the external demands are not enough to determine a profile nor to serve as parameters for the training prescription for athletes of the modality.